From Ideological Solitude to a Dialogical Encounter: F. Ebner, L. Althusser, P. Freire - Krzysztof Skorulski (University of Lower Silesia, 2014)
In this article two basic human situations are juxtaposed: the situation of a relationship with another human being (a dialogue) and the situation of human loneliness, characterized here as ideology. Their juxtaposition is based on the concepts of three outstanding, though very different, thinkers, combining philosophy and pedagogical activity. They are Ferdinand Ebner, Louis Althusser, and Paulo Freire. Ebner represents here the philosophy of dialogue, thus the trend perceiving the natural condition of man (to somewhat simplify it) in a dialogic situation. Althusser, as a neo-Marxist, sees the same condition in the immersion in ideology. In contrast, Freire - the developer of the "pedagogy of dialogue" - is trying to present a possibility to move from enslavement in ideology to freedom in dialogue. On the basis of this diversity of concepts an attempt is made to determine the "conditions of the possibility" to move from ideology to dialogue, and therefore also from enslavement to freedom. Particular importance is attributed to the issue of trust, the issue of "breaking natural life" (Ebner's term), and the question of the use of violence. When asked about the possibility of living in freedom and emancipation in a world infected with ideology, one cannot answer at the general and "objective" level, but in each case at the personal and subjective one. Thus, a desire to completely eliminate ideology would be perhaps fairly illusory, but it seems possible, despite the presence of ideology, to be aware of this presence and to choose a real person instead of it.